Developing Entrepreneurship Skills Management of Students at SMK 2 Palangka Raya - Iin Nurbudiyani; Muhammad Said (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2015)
Abstract The study seeks to trace the way of disseminating the skills of entrepreneurship among of the students in school (SMK Negeri) 2 Palangka Raya. This study applied qualitative approach by observation, documentation and interviews the principle of school, vice principle for curriculum affairs, vice principals for students affairs entrepreneurial education teacher, and unit production managers. The findings show that developing skills of students entrepreneurship has meer the criteria and functions of contemporary management. The ddissemination of entrepreneuership skills to the students was done through practical way through a variety of channels, such as units of production practice, in collaboration with the real enterprises such as telecommunication, pharmacy store, college of management and communication science, bazaar or flea market and other forms of collaboration with the tellecominication office, gra pari, and salon. In practice, disseminiting the entrepreneuership skills are still faced with many complex challenges such as human resources who has no progressive spirit of teaching due to the contemporary dynamics issues of business,lack professionalism of teacher in teaching and learning process, the curriculum change, lack of facilities and infrastucture owned by the school, and the limitation of time in practicing the theories. Abstrak Study ini mengkaji cara menanamkan ketrampilan berwirausaha pada siswa Sekolah Menengah Kejuruan Negeri 2 Palangka Raya. Studi ini menerapkan pendekatan kualitatif dengan observasi, dokumentasi, dan wawancara kepala sekolah, wakil kepala sekolah bagian kurikulum, wakil kepala sekolah bagian kesiswaan, guru kewirausahaan, dan pengelola unit produksi. Temuan studi ini menunjukkan bahwa pengembangan ketrampilan berwirausaha siswa telah memenuhi kriteria penerapan fungsi manajemen komtemporer. Diseminasi ketrampilan berwirausaha siswa selain pemahaman teorertik melalui proses belajar mengajar di kelas juga melalui praktek langsung beresentuhan dengan dunia usaha melalui sejumlah saluran yang berbeda seperti praktek di unit produksi, kerjasama dengan telekomunikasi, apotik, sekolah tinggi ilmu manajemen dan komunikasi, pasar murah, dan bentuk kerjasama lain seperti gra pari dan salon. Dalam prakteknya, diseminasi ketrampilan berwirausaha masih diperhadapkan dengan berbagai tantangan seperti sumber daya manusia yang memiliki semangat berkemajuan untuk mengajar sesuai dengan dinamika isu-isu business kontemporer, kurangnya profesionalisme guru, Perubahan kurikulum, kurangnya fasilitas dan infrasktuktur sekolah, keterabatasan waktu dalam mempraktekkan teori-teori kewirausahaan. How to Cite : Nurbudiyani, I. Said, M. (2015). Developing Entrepreneurship Skills Management of Students at SMK 2 Palangka Raya. TARBIYA: Journal Of Education In Muslim Society, 2(2), 131-145. doi:10.15408/tjems .v2i2.3182. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v2i2.3182